TEMPERATURE MAPPING OF PETRA CHRISTIAN UNIVERSITY MAIN CAMPUS SURABAYA - JUNIWATI Anik; KRISTANTO Luciana; WIDIGDO Wanda K. (Dimensi: Journal of Architecture and Built Environment, 2015)
Petra Christian University (PCU) is a university in Siwalankerto, a suburban area of Surabaya city, East Java-Indonesia. It is well developed at Siwalankerto that has been crowded with surrounding buildings. This research objective is to find the temperature mapping of PCU. The method is used by calculating all the land coverings including the built areas, the pavements, the green areas, mapped by the Screening Tool for Estate Environment Evaluation software-STEVE tool. The field measurement was also conducted. The results then be analyzed, which lands cover that gives more impact to the ambient air temperature. The climate components reviewed are the minimum, the average and the maximum ambient air temperature in degree Celcius. This research found that the lowest ambient air temperature mapped both by field measurement and STEVE-tool is the Zone 5; while the highest ambient air temperature of the STEVE-tool is the Zone 4; but from the field measurement found that the hottest is the Zone 3. This different results give an input for later STEVE-tool improvement.